PENGARUH VIDEO TUTORIAL TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI MATA PELAJARAN TEKNIK PEMESINAN BUBUT SMKN 2 MAKASSAR - Ahmad Ahmad; Mawardi Mawardi; Ahmad Afandi; Asriadi K (Journal of Innovation Research and Knowledge, 2022)
This study aims to: (1) explain the description of learning outcomes, (2) determine the effect of using video tutorial media on learning outcomes. The research method is quantitative research with experimental research types. The research design used was pre- experimental. The population in this study were class XI and Class XII students who studied 59 machining lathe techniques. The sample of this research is class XI as many as 27 people taken by purposive sampling technique. The results showed that: (1) learning outcomes with the use of video tutorial media have increased, this can be seen in the difference in the average value of the pre-test of 55.11 and post-test of 74.67, namely 19.56. In addition, the average normalized gain in learning outcomes is in the moderate category with an average of 0.47, this means that overall students experience a significant increase in learning outcomes, (2) the effect of video tutorial media on learning outcomes can be seen with paired sample t- test with a significance of less than 0.05, which means student learning outcomes have increased significantly.